Comparison between hydrometer and laser diffraction methods in the determination of clay content in fine-grained soils. Issue 1 (April 2021) - Lopez, A; Gustavsson, H; Korkiala-Tanttu, L
Abstract: Clay content is the main characterizing parameter when classifying fine-grained soils. Hydrometer method (HD) is commonly used in geotechnics to obtain the grain size distribution properties of fine-grained soils. However, this test is laborious and time consuming as compared to alternative methods such as laser diffraction (LD). In this study, a comparison between the results for clay content of 19 samples from different locations in Finland using HD and LD methods was carried out aiming at obtaining a mathematical expression that allows to transform LD measurements into HD results. The results were statistically compared showing significant differences between the results of these two techniques and underestimation of the clay content by the LD method was observed. Based on the results, the reliability of the laser method in the determination of clay content is discussed.